Tempo, Scale, Times: The Long Duration Narrative of Tamara Kamenszain (Anclajes, 2022)
The edition of La novela de la poesía (2012) already made evident two fundamental issues in Tamara Kamenszain's writing: on the one hand, a specific inscription of the passage poetry/novel/essay; on the other, the book (the edition, the support, the object) as a link. More recently, El libro de Tamar (2018) and Libros chiquitos (2020) illuminate in a special way two other constitutive aspects of the process: one, the temporal spiral between the program of the 70s and the present of writing, which converts the series in a long duration narrative; two, the problem of limits in the form of scale. In this paper I propose to read, at the intersection of El libro de Tamar and Libros chiquitos, three scenes as inflections in a long duration story with the test of time and limits: the tempo of the prose (the writing of the poem as the rhythm of the narrative and the prose as the distillation of the real of the verse), the magnitudes of the book (the book and the masterpiece of the 70s, the poetics of the little books as a inflection of the contemporary sublime), the intersection between the inscription of the present and the creation of a community.
Keywords: Tamara Kamenszain; Contemporary Argentine poetry; Contemporary Argentine Narrative; Contemporary Argentine essay; Temporalities